A Formulasi dan Evaluasi Sediaan Shampoo Ekstrak Daun Mint (Mentha piperita L.) - Rahadian, Daffa Alvara (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2024)
ABSTRACT Introduction: Mint leaf is a plant that can moisturize the skin, remove dead skin cells, smooth the skin and there are compounds that can control excess oil, containing anti-fungal compounds, namely saponins, tannins, flavonoids, and essential oils. The purpose of this study was to determine the metabolite compounds and the characteristics of the extract, to formulate a shampoo preparation of mint leaf extract based on na-cmc and to evaluate shampoo preparations. Methods: The evaluation of the ethanol extract was the metabolite test, the ethanol free test, the ash content test and the water content test. The mint leaf formulation was carried out with a concentration difference of 5% and 10%, then the evaluation included organoleptic tests, pH tests, viscosity tests, high foam tests, and hedonic tests. Result: The results of the metabolite test showed positive results on flavonoids, saponins, tannins, and terpenoids, the ethanol free test found negative results, the ash content and water content tests met the requirements of SNI. The results of the evaluation of the mint leaf extract shampoo formula on the organoleptic test, pH test, viscosity test, high foam test were found to be stable for 2 weeks, and in the hedonic test the results were more favorable to the formula with a concentration of 10%, the mint leaf extract formula was dark green, distinctive aroma menthol, thick liquid. Conclusion: The results of the study concluded that the evaluation of the extract and the evaluation of the formulation had met the criteria and requirements of SNI (06-2692-1992) for shampoo preparations. Keyword: Shampoo, Mint Leaf (Mentha piperita L.), Na CMC.